Prostate epithelial AR inactivation leads to increased intraprostatic androgen synthesis. Issue 3 (13th September 2012) - McNamara, Keely M.; Nakamura, Yasuhiro; Sasano, Hironobu; Handelsman, David J.; Simanainen, Ulla
Abstract BACKGROUND Regulation of steroid synthesis within the prostate is not well understood. In this study, we examined androgen synthesis and metabolism in the mouse prostate. METHODS Using LC–MSMS steroid assays, immunohistochemistry and real‐time PCR we examined the role of prostate epithelial AR in regulating 5αR expression and subsequent androgen metabolism by analyzing natural differences in epithelial AR expression between lobes as well as in the prostate epithelial AR knockout (PEARKO) mouse model. Subsequently, the role of intraprostatic androgen metabolism and epithelial AR in the generation and progression of prostate epithelial pathology was examined using long‐term exogenous testosterone (T) + estradiol (E2) exposure. RESULTS Epithelial AR and 5αR2 expression as well as intraprostatic DHT followed the same lobe‐specific pattern being lower in anterior than the other lobes (n = 6–8, P < 0.05). Lobe‐specific 5αR2 expression was similar in PEARKO and wild‐type (WT) prostate. However, PEARKO prostate had higher intraprostatic DHT content with significantly increased 5αR2 expression localized in abnormal epithelium. T + E2 treatment induced epithelial pathology was more common in PEARKO prostate compared to WT (20% vs. 2%), and was associated with increased 5αR2 expression (n = 6, P < 0.001). CONCLUSIONS We suggest that androgen synthesis via 5αR2 expression is driven by its own product (DHT) acting on adjacent stromal cells in a paracrine loop leading to increased in situ androgen levels in the PEARKO prostate. This may form part of a feed‐forward loop that promotes the development of epithelial pathology. Prostate 73: 316–327, 2013. © 2012 Wiley Periodicals, Inc.